2018
DOI: 10.1002/hep.29569
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of obeticholic acid monotherapy in patients with primary biliary cholangitis

Abstract: Obeticholic acid (OCA), a potent farnesoid X receptor agonist, was studied as monotherapy in an international, randomized, double‐blind, placebo‐controlled phase 2 study in patients with primary biliary cholangitis who were then followed for up to 6 years. The goals of the study were to assess the benefit of OCA in the absence of ursodeoxycholic acid, which is relevant for patients who are intolerant of ursodeoxycholic acid and at higher risk of disease progression. Patients were randomized and dosed with plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
193
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(195 citation statements)
references
References 34 publications
2
193
0
Order By: Relevance
“…During cholestasis, FXR signaling mediates an adaptive response aiming to reduce bile acid pool size by inhibiting bile acid synthesis and modulating their transport . FXR currently represents a promising target for therapeutic approaches to treat human cholestatic disease . Regulation of FXR involves a dynamic deacetylation process coordinated by SIRT1 and is needed for FXR‐DNA binding and target gene transcription, whereas the same process regulates FXR proteasomal degradation .…”
Section: Discussionmentioning
confidence: 99%
“…During cholestasis, FXR signaling mediates an adaptive response aiming to reduce bile acid pool size by inhibiting bile acid synthesis and modulating their transport . FXR currently represents a promising target for therapeutic approaches to treat human cholestatic disease . Regulation of FXR involves a dynamic deacetylation process coordinated by SIRT1 and is needed for FXR‐DNA binding and target gene transcription, whereas the same process regulates FXR proteasomal degradation .…”
Section: Discussionmentioning
confidence: 99%
“…Another phase 2 study launched simultaneously evaluated two OCA doses (10 mg and 50 mg) versus placebo as monotherapy in 59 patients with PBC. Serum ALP dropped by 53.9% in the 10‐mg group, 37.2% in the 50‐mg group, and by only 0.8% in the placebo group . Again, pruritus was the most important adverse event, leading to discontinuation of 38% of study subjects in the 50‐mg arm.…”
Section: Therapy For Pbcmentioning
confidence: 94%
“…As is characteristic of all cholestatic liver diseases, the degree of ALP elevation is higher than the degree of aminotransferase elevation in PBC. ALP typically ranges from 2 to approximately 10 x ULN, although ALP may be normal in the early stages of disease . While mean ALP values most commonly range between 2‐3 × ULN, a recent study from Mexico comparing survival rates of patients treated with ursodeoxycholic acid compared with other treatments, reported that entry ALP prior to the start of either ursodeoxycholic acid or other drugs was 5.2 ± 3.7 × ULN and 4.0 ± 4.5 × ULN (mean ± SD) in the two groups respectively .…”
Section: Hepatic Eligibility Criteria For Patients With Pbcmentioning
confidence: 99%
“…Obeticholic acid has now been listed on livertox.nih.gov as “a suspected rare cause of clinically apparent liver injury occurring mostly in patients with preexisting cirrhosis”0 . In reviewing published clinical trials of obeticholic acid for PBC, it is noted that there were discontinuations due to elevated liver tests, although the profiles of these patients were not publicly available for evaluation …”
Section: Obeticholic Acid and Potential Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation